Selection, drift, and constraint in cypridinid luciferases and the diversification of bioluminescent signals in sea fireflies. Issue 8 (5th November 2020) - Hensley, Nicholai M.; Ellis, Emily A.; Leung, Nicole Y.; Coupart, John; Mikhailovsky, Alexander; Taketa, Daryl A.; Tessler, Michael; Gruber, David F.; De Tomaso, Anthony W.; Mitani, Yasuo; Rivers, Trevor J.; Gerrish, Gretchen A.; et al.
Abstract: Understanding the genetic causes of evolutionary diversification is challenging because differences across species are complex, often involving many genes. However, cases where single or few genetic loci affect a trait that varies dramatically across a radiation of species provide tractable opportunities to understand the genetics of diversification. Here, we begin to explore how diversification of bioluminescent signals across species of cypridinid ostracods ("sea fireflies") was influenced by evolution of a single gene, cypridinid‐luciferase. In addition to emission spectra ("colour") of bioluminescence from 21 cypridinid species, we report 13 new c‐luciferase genes from de novo transcriptomes, including in vitro assays to confirm function of four of those genes. Our comparative analyses suggest some amino acid sites in c‐luciferase evolved under episodic diversifying selection and may be associated with changes in both enzyme kinetics and colour, two enzymatic functions that directly impact the phenotype of bioluminescent signals. The analyses also suggest multiple other amino acid positions in c‐luciferase evolved neutrally or under purifying selection, and may have impacted the variation of colour of bioluminescent signals across genera. Previous mutagenesis studies at candidate sites show epistatic interactions, which could constrain the evolution of c‐luciferase function. This work provides important steps toward understanding the genetic basis of diversification of behavioural signals across multiple species, suggesting different evolutionary processes act at different times during a radiation of species. These results set the stage for additional mutagenesis studies that could explicitly link selection, drift, and constraint to the evolution of phenotypic diversification. Abstract : see also the Perspective by Danielle M. DeLeo and Heather D. Bracken#x02010;Grissom.